(untitled) (Applied Biological Research, 2023)
A year-long (March, 2017 to March, 2018) study targeting the water quality and monogenean parasitosis on the gills of two fish species [Oreochromis niloticus (n = 133) and Labeo calbasu (n = 122)] was carried out at three different locations of river Penna flowing through YSR Kadapa district, Andhra Pradesh (India). A total of four species of ectoparasitic monogeneans i.e., Cichlidogyrus sclerosus, Cichlidogyrus tilapiae and Scutogyrus longicornis from O. niloticus and Dactylogyrus fotedari from L. calbasu were detected. A significant correlation (p < 0.05) was found between the prevalence of monogeneans and some water quality parameters [e.g., temperature, alkalinity, total dissolved solids, total hardness, dissolved oxygen and calcium hardness] in all the fishes examined. Results revealed highest prevalence of monogenean infection during winter, rainy and summer seasons. Parasitosis was analyzed location-wise and fishes collected from Somasila backwaters were observed highly infected with monogeneans. The positive correlation existing between the monogenean infection and water quality variables in the two basic seasons has led to the conclusion that ectoparasitic monogeneans are good biological indicators in assessing the water quality of a water body.